Prevalence of Suicidal Ideation and Its Association with Positive Affect in Working Women: A Day Reconstruction Study - Tian, Lili; Yang, Ying; Yang, Huijing; Huebner, E. Scott (Frontiers in Psychology, 2017)
The suicide rate for females in China is the second highest worldwide, and China is the only country in the world in which the rate of suicides is higher for women than men. Affective instability has been shown to be a strong predictor of suicidal ideation, particularly among women. However, prior research has mainly focused on the impact of women’s negative affect on suicidal ideation, ignoring the influence of positive affect on suicidal ideation. Studies have revealed that hopelessness, which is 1.3 times more important than depression for explaining suicidal ideation, is driven more by low levels of positive affect than by high levels of negative affect. Although positive affect has also been found to be related to suicidal ideation, and it demonstrates independent, beneficial effects on mental health, much remains to be learned about the association between positive affective instability and suicidal ideation. Therefore, we investigated the prevalence of suicidal ideation among Chinese working women and explored the differences between working women with and without suicidal ideation in the intensity and daily variability of positive affect. A total of 222 young working women of ages 22 to 36 years (M=27.64, SD=3.73) were recruited from a free weekend psychology lecture. The women subsequently completed a daily diary Day Reconstruction Method (DRM) as well as a suicidal ideation questionnaire. We used hierarchical linear modeling (HLM) to analyze the data, and the results showed that: (1) 10.81% of participates reported suicidal ideation, the intensity of positive affect (happiness, warmth/friendliness, interest and relaxation/calmness) was significantly lower for women with suicidal ideation compared to women without suicidal ideation; (2) differing diurnal patterns of positive emotions were observed between women with and without suicidal ideation; women with suicidal ideation demonstrated a significantly lower trend of growth and a higher volatility in happiness, warmth/friendliness, relaxation/calmness. Given that lower intensity of positive affect and greater affective instability significantly predicted suicidal ideation in Chinese women, researchers should pay more attention to the role of positive affect in female suicide prevention research and intervention efforts in the future.